Representation of Modest Fashion Values in @ dwihandaanda Instagram Content (Semiotic Analysis Study Ferdinand de Saussure) - Pithaloka, Hanna; Fatma Ali, Nadhifa (Universitas Darussalam Gontor, 2024)
The second largest Muslim population in the world with 281 million people and a potential GDP of USD 5.1 billion per year in the halal economy sector including Modest Fashion. The role of millennial generationinfluencers such as ig @dwihandaanda has also contributed greatly to the Muslim fashion industry with 2 million followers, through her contents reflecting Islamic values as self-image and at the same time reaching the Muslim market in the country. The purpose of this study is to describe the signs (images, text, emojis,captions or visual elements) in creating meaning in each of its contents using Ferdinand de Saussure’’s communication theory which is divided into signifiers and signifieds related to meaning. The method used is a qualitative descriptive approach with an interpretive approach. It is concluded that the content conveys many messages of affection in the dynamics of child development, the clothes used reflect the philosophy of loose, neutral and elegant and modern modest fashion design. Visually, the colors of brown, white, and creamtones indicate a minimalist aesthetic that is often used by modest fashion brands. This content not only sells products but also lifestyle and daily life with emotional connection to consumers. The lifestyle philosophy in its content is in line with the target audience of Muslim women, such as religiosity, spiritual values of happiness and simplicity. Modest fashion is a representation of freedom from stigma, strong self-confidence in gentleness, inclusivity and adaptive to the needs of an active lifestyle and full of achievements in Islamic values. For further researchers, they can conduct a survey study on followers to understand their preferences for related UGC (User Generated Content). Keywords: Semiotic; Communication; Influenceur; Fashion Modest; Indonesia